Psychologiczne aspekty stosowania instytucji nadzwyczajnego obostrzenia ustawowego zagrożenia wobec sprawcy na gruncie art.178 § 1 K - Lisowska, Anna (Filozofia Publiczna i Edukacja Demokratyczna, 2015)
The pages of this publication attempt to take into account various factors that may affect the state of inebriation or intoxication of man. States depriving individual impact on their own action were also presented in the field of drug use high-grade products, as well as the capacity reduction that recognise the importance of the act or direct proceedings under their influence was predicted. Stressors were classified according to their severity in relation to the issue of the article. Mental disorders were listed that appear in response to a traumatic event. Symptoms of acute stress and its relationship with the person’s behaviour were shown. It highlighted the doubts that arise on particular issues. The possibility of settlement was signalled. At the conclusions, explored issues were summarized.